Narrowing of giant gastric perforation by purse-string suture before omental plugging - Usta, Sertac; Kayaalp, Cuneyt; Gozeneli, Orhan (Elsevier Sci Ltd, 2015)
Introduction: Timely diagnosis of the gastroduodenal perforation usually allows primary repair or resection. Treatment of a large gastric perforation is more difficult than the common duodenal ulcer perforation by plugging and usually requires agastric resection. On the other hand, gastric resection fora hemodynamically compromised patient in sepsis hasa high rate of anastomotic failure and mortality. Here, we described a practical surgical technique that can avoid emergency gastric resection in such situations. Presentation of case: A 83 year-old female admitted with peritonitis, severe sepsis and hemodynamic instability. After the diagnosis of hollow organ perforation and supportive therapy, laparotomy revealed a delayed and large (7 cm) gastric perforation. Instead of gastrectomy, we downsized the large defect by means of a purse-string suture around the perforation and made it suitable for the application of omental plugging. Discussion: The patients with poor performance status who are not suitable for the gastric resection, a free omental plug fixation to the narrowed perforation area by a purse-string suture can overcome the problem. Conclusion: This method can be keep in mind as a damage control surgery technique in the non-traumatic abdominal emergencies due to large gastric perforations. (C) 2015 The Authors. Published by Elsevier Ltd on behalf of IJS Publishing Group Limited. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Gastrointestinal perforation; Omental patch; Narrowing perforation